Survey of transmission scheduling methods in wireless sensor networks - Xiao-ling ZHANG; Wei LIANG; Hai-bin YU; Xi-sheng FENG (Tongxin xuebao)
According to the features of wireless sensor networks,the definition and general constraints for transmission scheduling were given,and design principles and classification methods were summarized.Meanwhile,the fundamental mechanism of each recent representative transmission scheduling algorithms was analyzed in detail.The characteristics,performance,and application areas of various transmission scheduling algorithms were adequately compared.Finally,the status of current research development was concluded and the challenging and open research issues were pointed out.